The Performance of Ca(OH)2 to Reduce the Plasticity Index and Increase the Shear Strength Parameter for Expansive Soil - Mila Kusuma Wardani; Putu Tantri K. Sari; Mafrita Refionasari (Journal of the Civil Engineering Forum, 2022)
The design on expansive soils can easily change in volume due to the influence of water content. This makes it necessary to consider soil improvement methods in the planning process to maintain the variation in the water content. One of these methods includes chemical stabilization, which is carried out by adding materials such as cement or lime. In expansive soils, stabilization efforts aim to reduce the plasticity index and increase the shear strength parameters. Therefore, this study focused on the addition of slaked lime (Ca(OH)2) to expansive soil in Lakarsantri, Surabaya. The stabilizing materials used contain calcium to form pozzolan in the clay and increase the bearing capacity parameter, which is variation in shear strength. The soil was taken at 2 points A and B with a different moisture content of 48.57% and 35.12%, as well as a high plasticity index value > 50% using a percentage (Ca(OH)2) of 6%-24% at a certain curing time. Based on the results, the plasticity index in the soil changed from very high to moderate with an optimum percentage value of 6% at 30 days of curing time. The optimum value of soil shear strength is (Ca(OH)2) 6% at 30 days of age in soil A, the cohesion value is 0.02 kg/cm2, and an internal shear angle of 36°. In soil B, the optimum shear strength obtained (Ca(OH)2) was 6% at the age of 10 days with a cohesion value of 0.14 kg/cm2 and an internal shear angle of 23.80°. Therefore, the results of this study show that the parameter of shear strength of the soil from the cohesion value showed that the cohesion value decreased with the addition of Ca(OH)2, while the internal shear angle increased.